2020
DOI: 10.1074/jbc.ra119.012078
|View full text |Cite
|
Sign up to set email alerts
|

Single-molecule imaging analysis reveals the mechanism of a high-catalytic-activity mutant of chitinase A from Serratia marcescens

Abstract: Chitin degradation is important for biomass conversion and has potential applications for agriculture, biotechnology, and the pharmaceutical industry. Chitinase A from the Gram-negative bacterium Serratia marcescens (SmChiA) is a processive enzyme that hydrolyzes crystalline chitin as it moves linearly along the substrate surface. In a previous study, the catalytic activity of SmChiA against crystalline chitin was found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 55 publications
2
17
0
Order By: Relevance
“…This difference is one of the reasons that CfCel6B showed a lower K m value than TrCel6A. However, quantitative comparison is not easy, because direct measurement of the k on for productive binding was difficult because of the low frame rate and localization precisions, similar to the case for our recent single-molecule fluorescence imaging of chitinase A from Serratia marcescens ( 21 ).…”
Section: Discussionmentioning
confidence: 85%
“…This difference is one of the reasons that CfCel6B showed a lower K m value than TrCel6A. However, quantitative comparison is not easy, because direct measurement of the k on for productive binding was difficult because of the low frame rate and localization precisions, similar to the case for our recent single-molecule fluorescence imaging of chitinase A from Serratia marcescens ( 21 ).…”
Section: Discussionmentioning
confidence: 85%
“…Brazilian Archives of Biology and Technology. Vol.63: e20200061, 2020 www.scielo.br/babt walls of some fungi [1,2]. Water-soluble, degraded form of chitin is valuable both for biomass conversion and biotechnological applications [3].…”
Section: Introductionmentioning
confidence: 99%
“…Serratia marcescens is one of the chitinase over-producer bacteria [2,18,19]. There are some studies to ameliorate the characteristics of chitinase from S. marcescens.…”
Section: Introductionmentioning
confidence: 99%
“…Using single-molecule imaging analysis, we previously determined the kinetic parameters of elementary reaction steps and the chemomechanical coupling mechanism of Sm ChiA. 12 14 Recently, we further revealed that the F232W and F396W mutations at the beginning and end of the substrate-binding catalytic cleft decrease the dissociation rate constant of productively bound enzyme and increase processivity, and result in high catalytic activity. 14 , 15 Based on the multiple sequence alignment of the Sm ChiA and 257 Sm ChiA-like proteins, we also found that neither Phe232 nor Phe396 are predominant but tryptophan.…”
Section: Introductionmentioning
confidence: 99%
“… 12 14 Recently, we further revealed that the F232W and F396W mutations at the beginning and end of the substrate-binding catalytic cleft decrease the dissociation rate constant of productively bound enzyme and increase processivity, and result in high catalytic activity. 14 , 15 Based on the multiple sequence alignment of the Sm ChiA and 257 Sm ChiA-like proteins, we also found that neither Phe232 nor Phe396 are predominant but tryptophan. Our previous study strongly suggested that amino acid sequence of Sm ChiA is not optimized for high hydrolytic activity during the process of evolution in the nature.…”
Section: Introductionmentioning
confidence: 99%